Mengelola Ketidakpastian Pembelajaran Jarak Jauh, Manajemen Resiko Dalam Administrasi Sekolah Digital - Mulya Eka Putri, Darma; , Irsyad; Setiawati, Merika (CV. ITTC INDONESIA, 2025)
The challenges of managing uncertainty in distance learning (PJJ) also emphasize the importance of integrated risk management (MR) within digital school administration. The sudden transition to distance learning, especially during a crisis like the pandemic, has exposed serious weaknesses in the education system, such as limited digital infrastructure, inadequate teacher and student preparedness, and academic integrity issues. Uncertainties in distance learning encompass operational risks (such as network and device limitations, and data security), pedagogical risks (teaching quality and student participation), and strategic risks (institutional resilience to disruption). Digital school administration provides a framework for increasing efficiency and transparency, but alongside its benefits, digitalization also brings new risks such as cyberthreats, data privacy breaches, and challenges in technology adoption. Therefore, an active and comprehensive risk management approach is essential to address these multiple uncertainties.